Answer :

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c


For the given equation



And either of their sum or difference = b


=


Thus the two terms are


Difference =


=


=


Product =


=


using


=



using



2x[2x + (a + b)] - (a - b)[2x + (a + b)] = 0


[2x - (a - b)][2x + (a + b)] = 0


[2x - (a - b)] = 0 or [2x + (a + b)] = 0


2x = (a - b) or 2x = - (a + b)



Hence roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses